Government termination and anti-defection laws in parliamentary democracies. Issue 3 (16th April 2022) - Nikolenyi, Csaba
Abstract: A growing number of parliaments around the world have adopted anti-defection laws that protect the unity of legislative party groups. Although they remain rare among established democracies, India, Israel, and New Zealand have enacted such legislation with important consequences for the politics of executive–legislative relations. The paper argues that the introduction of anti-defection laws in the three democratic legislatures can be understood as an attempt to keep governments safe from defections rather than reduce the overall frequency of party switching. As such, anti-defection laws constitute an important albeit often overlooked institutional source of government stability.